2020
DOI: 10.1007/s00394-020-02260-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a 2-year physical activity and dietary intervention on plasma lipid concentrations in children: the PANIC Study

Abstract: Purpose We studied the effects of a physical activity and dietary intervention on plasma lipids in a general population of children. We also investigated how lifestyle changes contributed to the intervention effects. Methods We carried out a 2-year controlled, non-randomized lifestyle intervention study among 504 mainly prepubertal children aged 6-9 years at baseline. We assigned 306 children to the intervention group and 198 children to the control group. We assessed plasma concentrations of total, LDL, HDL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…These observations are of potential clinical importance, since replacing saturated fat with polyunsaturated fat has been shown to decrease the plasma concentration of low-density lipoprotein cholesterol and to reduce the risk of coronary heart disease in adults (28) . We have earlier found that the diet and physical activity intervention decreased plasma levels of low-density lipoprotein cholesterol over 2 years in the present study sample (13) . These observations together suggest that the improved quality of dietary fat since childhood may help prevent cardiovascular diseases in adulthood.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These observations are of potential clinical importance, since replacing saturated fat with polyunsaturated fat has been shown to decrease the plasma concentration of low-density lipoprotein cholesterol and to reduce the risk of coronary heart disease in adults (28) . We have earlier found that the diet and physical activity intervention decreased plasma levels of low-density lipoprotein cholesterol over 2 years in the present study sample (13) . These observations together suggest that the improved quality of dietary fat since childhood may help prevent cardiovascular diseases in adulthood.…”
Section: Discussionsupporting
confidence: 57%
“…Adolescents in the intervention group may have been more likely to be aware of the recommended diet and misreport their diet towards these recommendations than those in the control group. However, the improved plasma fatty acid profile (12) and the decreased plasma levels of low-density lipoprotein cholesterol (13) after 2 years supported the improved diet quality assessed by food records in the intervention group. One also has to be aware that the season when the food record is filled may affect the dietary data.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In order to study how weight loss history contributed to changes in outcome measures during 1 year of intervention, we tested for the 'lifetime history of weight loss × time' interaction using the intention-to-treat principle, including all 2684 participants in the analyses. Linear mixedeffect model analysis was used, and for each of the outcome measures we tested several models with allowing/ignoring random intercept and random slope on subject and/or study province level [48]. The Bayesian information criterion (BIC) was used as a measure of model adequacy [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by recent data from the Special Turku Coronary Risk Factor Intervention Project for Children (STRIP) study, in which participants who received individualized dietary counselling from age 7 months to 20 years were more likely to have ideal total cholesterol levels 6 years later (at age 26 years) compared with controls. Moreover, shorter (2-year) family-based interventions may also be effective, as highlighted by findings from the Physical Activity and Nutrition in Children (PANIC) study, in which individuals receiving physical activity and dietary interventions saw reductions in LDL-C levels compared with controls. These data align with our previous work showing that body mass index may be a key determinant of lipid and lipoprotein tracking .…”
Section: Discussionmentioning
confidence: 99%